Response of Local Cowpea Varieties Southwest Maluku to Drought Stress on Germination Phase - Ritha Lusian Karuwal; Hermalina Sinay (BERITA BIOLOGI, 2022)
Drought stress is one of the agricultural problem, especially in dry land. Respone to drought stress of local cowpea varieties Southwest Maluku on germination phase had not been conducted. The aim of this study was to evaluate response of local cowpea varities to drought stress on germination phase. The research was using seven of local varieties (KM1, KM3, KM4, KM6, KM7, KM8, KM9) from Kisar island and three cultivars from ILETRI Malang. Treatment of drought stress were consist of watering period every twice days (P0) and five day (P1) was replicated three times. Sprout number, final germination percent, sprout length, sprout weight, vigor index and prolin content in root were observed. Data were analyzed using ANOVA, followed by DMRT at 5%. The results showed that treatment of every five day inhibit germination at all varieties. KM1, KM4, KM6 varieties has the highest value on all parameter. There are positive correlation which significant between of the observation parameter. Principal component analysis to clustering in two main cluster. Early selection of drought tolerance at germination phase very need to breeding plant in effort of the suistainble development and utilization.